Embodied Interpretation: Interpreting Gesture and Expression in Impromptu Op.29 No.1 in A-flat Major by Frédéric Chopin - Ruiyang, Chen; Kent, Tham Horng (Harmonia: Journal of Arts Research and Education, 2025)
This article aims to extend Hatten’s theory beyond the early nineteenth century by examining the different musical gestures in Impromptu Op.29 No.1 in A-flat Major by Frédéric Chopin. There is a need to bridge Hatten’s theoretical framework with its practical application in the Romantic piano repertoire. The current article adopts Hatten’s theory as a framework to provide detailed analyses of how stylistic (culturally embedded) and strategic (context-dependent) gestures operate within this impromptu. This study was conducted using a gestural analysis and performance-based research. It provides a guideline for pianists to develop their own interpretation. The findings suggest that Chopin’s Impromptu No.1 conveys a spontaneous, dialogical, thematic, rhetorical gesture that evokes a sense of improvisation. Findings also reveal that developing practical tools based on Hatten’s theory on musical gestures will help pianists articulate emotional expression, manage rubato, and enhance dynamic control, ultimately leading to more informed and expressive interpretations. This article offers performers the chance to gain insight into the piano practice, which further expands the scope of Hatten’s theoretical application to include the Romantic repertoire, thereby offering valuable contributions to gesture studies and performance analysis.